(untitled) - Fukuda, T. (Singapore,River Edge, N.J., 1994)
This work introduces various topics, from concepts to the latest research, on cellular and micro-robotic systems. The cellular robotic system is a self-organizing robotic system composed of a large number of autonomous robotic units, named "cells". This idea came from the organic structure of a living body. Several topics in this area are covered, such as swarm intelligence, communications and robotic mechanisms. Micro-mechanisms, control and intelligence, with respect to this system are treated here. The combination of both technologies will prepare the way for a new paradigm in the field of engineering.
Keywords: Robotics,Automatic control,Microelectronics,Người máy học,Điều khiển tự động